Validation of markerless motion capture system (OpenCap) for overhead squat kinematics - Yeom, S.; Jeong, B.; Lee, J.; Hyung, S.; Kim, H.; Chang, E.; Kim, K. (Measurement in Physical Education and Exercise Science, 2025)
This study validated OpenCap, a markerless motion capture system, by comparing its joint kinematics to those obtained from a conventional marker-based system during overhead squat movements. Twenty-two male subjects performed normal and simulated abnormal squats, with kinematic data recorded simultaneously by both systems. Validation metrics included waveform similarity, measured by the coefficient of multiple correlation (CMC), and error, quantified as root mean square error (RMSE). For lower body joints, OpenCap demonstrated high waveform similarity (mean CMC = 0.93) and low RMSE (5.45°), whereas upper body measurements were less accurate (mean CMC = 0.48; RMSE = 36.7°). Wilcoxon signed-rank tests revealed significant RMSE differences in knee, ankle, and hip angles between normal and abnormal conditions. These findings suggest that while OpenCap reliably captures lower body kinematics, further refinement is needed for upper body analysis and detecting abnormal movement patterns. Future algorithmic and hardware improvements may expand its clinical and sports applications.